Reference evapotranspiration (ETo) maps for California - Temesgen, Bekele, author; Frame, Kent, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
The California Irrigation Management Information System (CIMIS) manages over 130 active weather stations throughout the state. Archived data is also available for 75 additional stations that have been disconnected from the network. Most of these stations produce estimates of reference evapotranspiration (ETo) for the station location and their immediate surroundings. Because of California's diverse landmass and climate, however, many locations within the state lack a representative CIMIS station. Some counties, for example, do not have a CIMIS station at all and others have only one or two stations. As a result, there are significant spatial ETo data gaps. In an attempt to mitigate this problem, CIMIS initiated a project in 2003 to investigate the possibility of coupling remotely sensed satellite data with point measurements to generate spatially distributed ETo values. In cooperation with the University of California Davis's Center for Spatial Technologies and Remote Sensing (UCD CSTARS), CIMIS developed a model that derives daily solar radiation from the visible band of the National Oceanic and Atmospheric Administration's (NOAA) Geostationary Operational Environmental Satellite (GOES) and couples it with air temperature, relative humidity, and wind speed interpolated between point measurements from the CIMIS stations. Two interpolation methods, DayMet and Spline, are selected based on accuracy of results, code availability, and computational efficiency. Daily ETo values are calculated using the American Society of Civil Engineers version of the Penman-Monteith equation (ASCE-PM) at 2-km spatial resolution. The accuracy of the ETo estimate was tested using cross validation techniques and we are confident that this product will assist the people of California in saving water and energy.
USCID water management conference
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.